Hepatic Angiosarcoma Associated with Esophageal Variceal Hemorrhage - Zensho Ito; Mikio Kajihara; Yasunobu Kobayashi; Tomoya Kanai; Yoshihiro Matsumoto; Kazuki Takakura; Toyokazu Yukawa; Toshifumi Ohkusa; Seita Koyama; Hiroo Imazu; Hiroshi Arakawa; Mitsuru Ohata; et al. (Case Reports in Gastroenterology, 2016)
Primary hepatic angiosarcoma is a very rare malignancy with a poor prognosis. Because patients present with no specific symptoms, the cancer can grow undetected and most cases are diagnosed too late for resection. We present the case of a 78-year-old Japanese man admitted to our hospital with massive hematemesis and melena. A total gastrectomy had previously been performed on the patient to treat gastric cancer. Endoscopic injection sclerotherapy was performed to control the bleeding from varices over the anastomosis. Computed tomography revealed the presence of multiple atypical liver nodules in the enhanced image. Histological diagnosis of hepatic angiosarcoma was obtained by percutaneous ultrasound-guided liver biopsy. To our knowledge, this is the first report of a patient with hepatic angiosarcoma and acute variceal hemorrhage.